2004
DOI: 10.1254/jphs.fpj04007x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sphingosine 1-Phosphate-Induced Phospholipase C Activation During G0-G1 Transition in Rat Hepatocytes

Abstract: Abstract. We previously reported that sphingosine 1-phosphate (S1P) induces inhibition of adenylyl cyclase and activation of phospholipase C via independent G protein-coupled receptors in adult rat hepatocytes. Although S1P activation of phospholipase C and subsequent increase of intracellular Ca 2+ concentration were enhanced during the primary culture of hepatocytes, S1P inhibition of adenylyl cyclase remained unchanged. Here, we addressed whether enhancement of S1P-induced actions is dependent on change of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…S1P-induced Ca 2+ mobilization was increased in 24-h cultured hepatocytes, whereas Ins-P 3 -binding sites were decreased in the cells (11,15). Increased expression of S1P 2 receptor and increased production of Ins-P 3 could explain the increased Ca 2+ mobilization by S1P in 24-h cultured hepatocytes, although future studies need to elucidate why such an inefficient signaling pathway was used by S1P in 24-h cultured hepatocytes (11,14).…”
Section: +mentioning
confidence: 97%
See 1 more Smart Citation
“…S1P-induced Ca 2+ mobilization was increased in 24-h cultured hepatocytes, whereas Ins-P 3 -binding sites were decreased in the cells (11,15). Increased expression of S1P 2 receptor and increased production of Ins-P 3 could explain the increased Ca 2+ mobilization by S1P in 24-h cultured hepatocytes, although future studies need to elucidate why such an inefficient signaling pathway was used by S1P in 24-h cultured hepatocytes (11,14).…”
Section: +mentioning
confidence: 97%
“…3). In our previous studies, we showed that enhancement of S1P-induced PLC activation during hepatocytes culture was accompanied by increases of S1P-induced Ca 2+ response and phosphorylase activation (11) and also possible involvements of G-proteins and S1P 2 receptor in the S1P signaling pathway (11,14). However, S1P action on intracellular Ca 2+ stores was not directly measured.…”
Section: +mentioning
confidence: 99%
“…Alternatively, it is possible that cellto-cell contact in aortic myocytes has an obligatory role in enhancement. In rat hepatocytes, harvested cell density was critical in the up-regulation of S1P 2 expression during progression of the proliferating status (33). Moreover, S1P has an attachment-dependent regulatory effect on invasion of epithelial ovarian cancer cells, suggesting that phenotype-dependent change of extracellular matrix such as N-cadherin, gamma-and betacatenins, and / or integrins affects S1P-mediated Ca 2+ responses in cultured smooth muscle cells (37).…”
Section: +mentioning
confidence: 99%
“…Although we can not identify the mechanisms involved in the change of the S1P response, possibly followed by enhancement of S1P 3 expression during culture, this is the first evidence that S1P 3 is up-regulated during culture. S1P 1 expression was decreased in proliferating vascular endothelial cells and hepatocytes (32,33). Vascular endothelial growth factor (VEGF) induces the expression of S1P 1 in endothelial cells via tyrosine kinase-and protein kinase C-mediated pathways (34).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation